Peningkatan Cinta Lingkungan Di Masyarakat Pedesaan Melalui Program Pengabdian Masyarakat Di Desa Pangirkiran Tahun 2023 - Risna Hanani Lubis; Nur Adilah Nst; Nur Khofifah; Nurhajjah Pulungan; Imelda Zulfina Lubis; Sehati Khalisa Hsb; Nadya Wulansari; Ahmad Ardianyah Lubis; Zainul Imam (Pusat Riset dan Inovasi Nasional, 2024)
Real Work Lectures (KKN) aims to create a form of embodiment of the Tri Dharma of Higher Education, namely service, as an index of community development through work and concrete evidence. Real Work Lectures (KKN) are a form of real work in the community to empower rural communities designed by students who are able to lead students to become complete individuals with the guidance of a lecturer, both in utilizing knowledge, the ability to analyze the conditions of the surrounding community, and providing solutions in overcoming various social, economic, health, educational and political problems according to their scientific field. Judging from the problems that occur in the field, we created a Real Work Lecture (KKN) program divided into four areas which consist of education, religion, entrepreneurship, social environment, health and infrastructure. Data was collected through multimethods such as interviews, observation, documentation studies